Pediatric invasive pneumococcal disease caused by vaccine serotypes following the introduction of conjugate vaccination in Denmark. - Zitta B Harboe; Palle Valentiner-Branth; Helene Ingels; Jeppe N Rasmussen; Peter H S Andersen; Catherine C Bjerre; David Goldblatt; Lindsey Ashton; Mitch Haston; Helle B Konradsen; Lotte Lambertsen; Danish Pneumococcal Surveillance Collaborating Group (PLoS ONE, 2013)
A seven-valent pneumococcal conjugate vaccine (PCV7) was introduced in the Danish childhood immunization program (2+1 schedule) in October 2007, followed by PCV13 starting from April 2010. The nationwide incidence of IPD among children younger than 5 years nearly halved after the introduction of PCV7 in the program, mainly due to a decline in IPD caused by PCV7-serotypes. We report the results from a nationwide population-based cohort study of laboratory confirmed IPD cases in children younger than 5 years during October 1, 2007 to December 31, 2010 and describe the characteristics of children suspected to present with a vaccine failure. The period between April 19 and December 31, 2010 was considered a PCV7/PCV13 transitional period, where both vaccines were offered. We identified 45 episodes of IPD caused by a PCV7 serotype (23% of the total number) and 105 (55%) caused by one of the 6 additional serotypes in PCV13. Ten children had received at least one PCV7 dose before the onset of IPD caused by a PCV7 serotype. Seven children were considered to be incompletely vaccinated before IPD, but only three cases fulfilled the criteria of vaccine failure (caused by serotypes 14, 19F and 23F). One case of vaccine failure was observed in a severely immunosuppressed child following three PCV7 doses, and two cases were observed in immunocompetent children following two infant doses before they were eligible for their booster. None of the IPD cases caused by the additional PCV13 serotypes had been vaccinated by PCV13 and there were therefore no PCV13-vaccine failures in the first 8-months after PCV13 introduction in Denmark.